Petroleum System Modeling of a Fold and Thrust Belt: A Case Study from the Bannu Basin, Pakistan - Afzal Mir; Muhammad Rustam Khan; Ali Wahid; Muhammad Atif Iqbal; Reza Rezaee; Syed Haroon Ali; Yucel Deniz Erdal (Energies, 2023)
This study focused on analyzing the petroleum system of the Bannu Basin, which is the foreland basin of the Himalayan fold and thrust belts in Pakistan. The objectives of this study were achieved by dividing the study area into three zones, namely, the Southwestern zone, Southeastern zone, and Northeastern zone. The regional 2D seismic lines and well log data, including the bore hole temperature (BHT) and petrophysical and geochemical data, were integrated. The seismic interpretations and geohistory plots indicate higher levels of sedimentation and abrupt sedimentation from the Miocene until the Recent era due to the initiation of Himalayan orogeny. The thermal modeling indicates that potential source rocks are present in the basin, whereas the local faults in the Southwestern and Southeastern zones act as potential traps for the preservation of hydrocarbons. It is assumed that the Tredian Formation and Lumshiwal Formation are the potential reservoir rocks in the Southwestern zone, whereas the Warcha Formation and Tredian Formation are the economic reservoirs in the Southeastern zone. However, in the Northeastern zone, no major accumulation is present. The significant sedimentation of post-Miocene formations was the major event for the generation of hydrocarbons and a critical moment for the accumulation of hydrocarbons in the study area.